2019
DOI: 10.1111/1759-7714.13197
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring antibody binding to T cells in a pembrolizumab‐treated patient with lung adenocarcinoma on hemodialysis

Abstract: Recent clinical trials have demonstrated that anti‐PD‐1 blocking antibodies showed remarkable clinical efficacy in a subset of non‐small cell lung cancer (NSCLC) patients. Clinical trials usually exclude patients with renal dysfunction who are receiving hemodialysis (HD). Therefore, it is unclear whether these patients can be safely and effectively treated with pembrolizumab. Here, we present a non‐small cell lung cancer patient on HD who achieved complete remission after one dose of pembrolizumab without seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Furthermore, it has been suggested that both cisplatin and carboplatin have a role in promoting antitumor immune responses by reducing the number of myeloid-derived suppressor cells [41,42]. Of particular note, it is also suggested that cisplatin not only enhances T-cell activity, but also induces tumor cell PD-L1 upregulation, thus possibly accounting in part for the additive antitumor activity between cisplatin-based chemotherapy and PD-L1/ programmed death protein-1 (PD-1) inhibition [37,[43][44][45]. Indeed, the expression of PD-L1 in NSCLC cells is shown to be upregulated following preoperative cisplatin-based chemotherapy in NSCLC patients (before vs after chemotherapy, 11% vs 26%; p = 0.017) [36].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been suggested that both cisplatin and carboplatin have a role in promoting antitumor immune responses by reducing the number of myeloid-derived suppressor cells [41,42]. Of particular note, it is also suggested that cisplatin not only enhances T-cell activity, but also induces tumor cell PD-L1 upregulation, thus possibly accounting in part for the additive antitumor activity between cisplatin-based chemotherapy and PD-L1/ programmed death protein-1 (PD-1) inhibition [37,[43][44][45]. Indeed, the expression of PD-L1 in NSCLC cells is shown to be upregulated following preoperative cisplatin-based chemotherapy in NSCLC patients (before vs after chemotherapy, 11% vs 26%; p = 0.017) [36].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we administered carboplatin (AUC = 5, 125 mg/body on day 1), etoposide (40 mg/m 2 on days 1, 2, and 3), and atezolizumab (1200 mg on day 1). The results of previous reports on PD-1/PD-L1 inhibitor for LC patients on HD are summarized in Table 1 [11][12][13][14]. It is not clear how dialysis affects the blood levels of each drug as the blood concentration was not measured.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that synergy exists between immune checkpoint inhibitors and chemotherapy. In a previous study, the duration of pembrolizumab, a PD-1-blocking antibody, in T cells of non-small-cell lung cancer patients was systematically assessed, and complete binding to T cells was reportedly lost after approximately 20 to 25 weeks ( 24 ). Anti-PD1 also may provide a delayed synergistic effect on subsequent cytotoxic therapy and may contribute to improved therapeutic efficacy through the overlap of circulating anti-PD1 and cytotoxic agents.…”
Section: Discussionmentioning
confidence: 99%